ANALYSIS OF THE PROBLEM OF PROFESSIONALISM AND PERSONAL AUTHORITY - Yuldasheva Saodat Mamasaxatovna (Modern American Journals, 2025)
The scientific goal of the study of the topic is to offer a scientific analysis useful in identifying and improving scientific solutions for the interrelationships of professionalism and personality potential, problems related to them, and their development. The subject will be a key contributor to the description of academic research related to learning, practice development, and skills.
Keywords: Problems of professionalism, pedagogical-psychological research, professional skills, activity and communication.